IMPLEMENTASI CCTV ONLINE UNTUK MENINGKATKAN PEMANTAUAN FASILITAS WARGA BANJAR SAMPALAN - Rudiastari, Elina; Ari Dwi Suta Atmaja, I Made; Bagus Catur Bawa, I Gusti Ngurah; Triana Indah, Komang Ayu; Ayu Sukerti, Gusti Nyoman; Arya Astawa, I Nyoman Gede (Jurnal Praksis dan Dedikasi Sosial, 2024)
IMPLEMENTATION OF ONLINE CCTV TO IMPROVE MONITORING OFBANJAR SAMPALAN RESIDENTS' FACILITIES Sampalan Hamlet is a tourist destination where many facilities and infrastructure have begun to be built. The problems faced by the Sampalan Traditional Banjar are that there is no supervision of the routes around the Banjar area, there is no documentary evidence that can be used to analyze accidents that occur around the Banjar, there is no supervision to avoid acts of theft at the temple and there is no supervision of the social activities of residents which was carried out in Banjar. The solution offered in this community service activity for the problems experienced is the installation of CCTV. This service activity aims to help access monitoring and supervision of the Banjar area to increase the security and comfort of residents and visiting tourists. This method of implementing community service activities is implemented into three main stages, namely preparation, implementation and evaluation. The results of the evaluation through a questionnaire resulted in 71.4 percent of residents stating that the installed CCTV was very useful, and 50 percent of residents stated that the presence of CCTV greatly facilitated monitoring and supervision around the Banjar. Dusun Sampalan merupakan destinasi wisata dimana fasilitas serta infrastruktur sudah mulai banyak dibangun. Permasalahan yang dihadapi Banjar Adat Sampalan yaitu belum adanya pengawasan terhadap jalur disekitar areal Banjar, tidak adanya bukti dokumentasi yang dapat digunakan untuk menganalisa peristiwa kecelakaan yang terjadi di sekitar Banjar, tidak adanya pengawasan untuk menghindari tindakan pencurian di pura serta tidak adanya pengawasan terhadap aktivitas sosial warga yang dilakukan di Banjar. Solusi yang ditawarkan dalam kegiatan pengabdian kepada masyarakat ini untuk permasalahan yang dialami adalah pemasangan CCTV. Tujuan dari kegiatan pengabdian ini adalah membantu akses monitoring dan pengawasan areal Banjar sehingga meningkatkan keamanan dan kenyamanan warga serta wisatawan yang berkunjung. Metode pelaksanaan kegiatan pengabdian kepada masyarakat ini diimplementasikan menjadi tiga tahapan utama yaitu persiapan, pelaksanaan dan evaluasi. Hasil evaluasi melalui kuisioner menghasilkan 71,4 persen warga menyatakan CCTV yang terpasang tersebut sangat bermanfaat serta 50 persen warga menyatakan bahwa adanya CCTV sangat mempermudah monitoring dan pengawasan di sekitar Banjar.